The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3233/ch-211322
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and uric acid/creatinine ratio and their correlations with the hemorheological determinants in subjects with subclinical carotid atherosclerosis

Abstract: BACKGROUND AND OBJECTIVE: we have examined the concentration of serum uric acid and the serum uric acid/creatinine ratio as well as their correlations with the main determinants of the hemorheological profile in a group of subjects with subclinical carotid atherosclerosis. METHODS: we evaluated the concentration of serum uric acid and the serum uric acid/creatine ratio in 43 men and 57 women [median age 66.00 (25)] with subclinical carotid atherosclerosis, subsequently divided according to the number of tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…40 Physicians should also pay attention to patients with high SUA/SCr values, while uric acid is normal and employs protective strategies such as serum uratelowering and renal protection therapies. 41 Additionally, we found that diabetes mellitus, hypertension, antiplatelet drug usage at discharge, and smoking status were associated with stroke recurrence in young adults. Sarecka-Hujar et al conducted a literature review and found that hypertension and diabetes mellitus were more prevalent in young patients with recurrent stroke.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…40 Physicians should also pay attention to patients with high SUA/SCr values, while uric acid is normal and employs protective strategies such as serum uratelowering and renal protection therapies. 41 Additionally, we found that diabetes mellitus, hypertension, antiplatelet drug usage at discharge, and smoking status were associated with stroke recurrence in young adults. Sarecka-Hujar et al conducted a literature review and found that hypertension and diabetes mellitus were more prevalent in young patients with recurrent stroke.…”
mentioning
confidence: 75%
“… 40 Physicians should also pay attention to patients with high SUA/SCr values, while uric acid is normal and employs protective strategies such as serum urate-lowering and renal protection therapies. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Other components of Yiqingfang, such as naringenin and diosgenin, can reduce the expression of HIF-1 and VEG-FA, decrease lipid synthesis and inflammatory response, and enhance the level of autophagy [13,14]. According to the "renal overload" theory [15], the intestinal tract plays a key role in the homeostatic regulation of blood uric acid levels, and abnormalities in intestinal and renal function firstly lead to a sustained increase in uric acid levels, which in turn triggers a vicious cycle of tissue damage and uric acid accumulation in the body [16].…”
Section: Discussionmentioning
confidence: 99%